Exploring the Use of AI-Based Speech Recognition Platforms to Support Elementary Students’ Speaking Skills in Distance Learning - Saddam Fathurrachman (Institut Agama Islam Negeri Parepare, 2026)
This study explored the use of Google Assistant as an AI-based speech recognition tool to support elementary students’ speaking skills in distance learning. The study employed a descriptive qualitative approach involving 30 sixth-grade students, 5 teachers, and 2 parents from two primary schools in Indonesia during June–July 2025. The data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed thematically using Braun and Clarke’s framework to identify patterns in students’ speaking practice, perceptions, and the challenges encountered during implementation. The findings demonstrated that Google Assistant functioned as an interactive digital scaffold, providing students with flexible opportunities for repeated oral practice. Furthermore, students predominantly perceived the platform as a supportive, low-pressure, and enjoyable tool that significantly boosted their speaking confidence. However, the implementation revealed technical and pedagogical challenges, particularly regarding unequal device access, internet connectivity issues, and the necessity for clear instructional design. The study concludes that AI-based speech recognition tools hold substantial pedagogical potential for elementary distance learning, provided they are integrated within a supportive ecosystem involving active teacher facilitation and parental involvement.